School, gender and ideological incest - Mazeres Gaitero, Francisco Javier (2021)
Among the effects that the current pandemic cycle seems to be having on the national public education agenda is that it has eclipsed the debate on comprehensive sexuality education (CSE). This synthesizes like few others the sensitive relationship between religion and politics in a genuinely religious country like Peru (Romero, 2016) but also expresses the impulse of certain sectors of civil society to deepen a process of secularization of the State that institutionalizes the advances in rights and freedoms of the different minority groups in our society.